Students’ Attitudes and Performance in Mathematics in Secondary Schools in Kakira Town Council in Jinja District. - Kasononta, Ronald (Kabale University, 2024)
The attitude of students towards mathematics is a factor that is known to influence students’ learning and achievement in the subject. The purpose of this study was therefore to determine the effect of students’ attitude towards their learning and achievement in mathematics by first trying to establish their attitudes regarding the subject and finding out the factors that influence these attitudes. The study would provide some of the learners’ behaviors as a result of their attitude toward the subject and would go a long way in helping the learners to develop a positive attitude toward the subject which is a recipe for better learning performance and achievement in the subject. The study involved five secondary schools in Jinja district and the target population was mathematics teachers and four students. The purposive and random samplings were employed in selecting the schools, students, and teachers from those schools respectively with the use of student’s and teachers’ questionnaires as a method of data collection. The questionnaires were designed to capture some of the students’ and teachers’ perceptions and beliefs which were grouped according to themes including difficulty, liking, usefulness, and future expectations regarding the subject, learners’ mathematical ability, and achievement. The students and teachers responded to the questionnaires and data was collected, calculated, and converted into percentages. The study found out that most students had a positive attitude towards mathematics and that they perceived mathematics as doable, learnable, and important yet this did not translate to good grades. Also, teachers had some challenges in teaching mathematics which included negative attitudes towards mathematics by most of the students, particularly girls, this was a common challenge to all teachers who responded to the questions. The findings also show that perception and beliefs, perceived learning abilities and competencies, and previous performances of students in mathematics affected their level of motivation leading to low outcomes.